Overexpression of miR-484 and miR-744 in Vero cells alters Dengue virus replication - Juan Camilo Castrillón-Betancur; Silvio Urcuqui-Inchima (Memorias do Instituto Oswaldo Cruz)
BACKGROUND Dengue is considered one of the world’s most important mosquito-borne diseases. MicroRNAs (miRNAs) are small non-coding single-stranded RNAs that play an important role in the regulation of gene expression in eukaryotes. Although miRNAs possess antiviral activity against many mammalian-infecting viruses, their involvement in Dengue virus (DENV) replication remains poorly understood. OBJECTIVE To determine the role of miR-484 and miR-744 in DENV infection and to examine whether DENV infection alters the expression of both miRNAs. METHODS We used bioinformatics tools to explore the relationship between DENV and cellular miRNAs. We then overexpressed miR-484 or miR-744 in Vero cells to examine their role in DENV replication using flow cytometry, reverse transcriptase quantitative polymerase chain reaction (RT-qPCR), and western blotting. FINDINGS We found several cellular miRNAs that target a conserved region within the 3′ untranslated region (3′ UTR) of the genome of the four DENV serotypes and found that overexpression of miR-484 or miR-744 inhibits infection by DENV-1 to DENV-4. Furthermore, we observed that DENV RNA might be involved in the downregulation of endogenous miR-484 and miR-744. CONCLUSION Our study identifies miR-484 and miR-744 as two possible restriction host factors against DENV infection. However, further studies are needed to directly verify whether miR-484 and miR-744 both have an anti-DENV effect in vivo.